(untitled) - Jackie Maguire (Oxford, 2000)
In Britain, Canada and the USA, in each of the four seasons, people enjoy different festivals and celebrations. Food, family and flowers are an important part of most celebration. Christmas, Easter, Valentine's Day and the Four of Julay. These are all inportant days in English-speaking countries? But how do people celebrate them? And why do children go " trick or teating " in October or burn " guys " in November? Why This book tells us some of these answers.
Keywords: almanacs,curiosities and wonders